Optimizing Replanting Strategies for Oil Palm Plasma: Financial Patterns and Farmer Concerns in South Sumatra, Indonesia - Wildayana, Elisa; Armanto, M Edi; Maryadi; Adriani, Dessy; Nearti, Yuwinti (Indonesian Soil Science Society of South Sumatra in Collaboration With Soil Science Department, Sriwijaya University, 2025)
This study examines the financial feasibility of different replanting patterns for oil palm plasma and assesses farmers’ concerns regarding replanting decisions. The research was conducted in three districts of South Sumatra (OKI, Muara Enim, and Musi Banyuasin) with plasma farmers as respondents. Three financing patterns were analyzed: self-financing through savings, insurance-based financing, and bank loans. The research used a survey method and sampling was determined with a balanced random sampling technique with 90 respondents. The research concluded that the financing pattern of oil palm replanting can be done through savings, insurance, and bank loans. The best financing pattern for replanting is conducted by using their savings because it can produce the highest net B/C value; NPV; and the shortest payback period. Sensitivity analysis showed that Fresh Fruit Bunch (FFB) price reduction is the most sensitive for the financing patterns of their savings and bank loans, however for the financing patterns of insurance, the decrease in FFB production is mentioned as the most sensitive. The government has to maintain stable FFB pricing, and it is advised that they use their funds, which are arranged by KUD, to support the oil palm replanting. Five factors -complexity, compatibility, relative profitability, trialability, and observability - will be used to gauge farmers’ concerns about oil palm replanting.